Pengaruh Lokasi Dan Keberagaman Produk Terhadap Minat Beli Konsumen Dengan Harga Sebagai Variable Moderasi Pada Umkm Di Sepanjang Jalan Semangka - Netty Laura; Maesaroh Afivah (Owner : Riset dan Jurnal Akuntansi, 2022)
It is not easy to make efforts in the open. It takes preparation and maturity in planning, especially if the company is going to be opened in the heart of the city, where there are always other MSMEs selling the same products. Destination conducted this research as an effort to assist SMEs in determining strategies in choosing the place and form of product variation to be sold, by investigating whether there is an influence of location and product diversity on buying interest with price as a moderating variable. The method used in this research is Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS (3.3.0) software. With data collection techniques and a widely distributed online questionnaire, 135 responses were collected. According to research findings, there is a positive and quite large effect of product diversity and price on buying interest. While location does not have a significant effect on buying interest, if moderated by price, location has a negative effect on buying interest.